A review of the drivers of tropical peatland degradation in South-East Asia. (December 2017) - Dohong, Alue; Aziz, Ammar Abdul; Dargusch, Paul
Highlights: A review of the drivers of peatland degradation in South-East Asia over the past 20 years. Categorises the activities into direct and indirect drivers of peatland degradation. Highlights the complex mix of indirect socioeconomic, policy and climate change. Provides key recommendation to address the issue and identifies future area of research. Abstract: The world's largest area of tropical peatland ecosystems is found in South-East Asia. These peatlands have globally significant carbon stocks and play an important role in regional and global climate systems. Despite the valuable social and economic services and ecosystem biodiversity these tropical peatlands provide, misguided land use policies have resulted in widespread peatland degradation in the region during the past 20 years. This paper reviews the drivers of peatland degradation in South-East Asia and confirms that logging, conversion to industrial plantations, drainage, and recurrent fires are the principal direct drivers of peatland degradation in South-East Asia, and that these drivers are compounded by a complex mix of indirect socioeconomic, policy- and climate change-related factors. The review concludes by noting that in order to address the problem of peatland degradation, we first need to know more about how to design and assess "successful" peatland restoration initiatives, and what regulatory and policy interventions are likely to improve peatland conservation and restoration outcomes in the South-East Asian region.